A Democracia como Objeto de Análise na Teoria das Relações Internacionais no Pós-Guerra Fria - Queiroz, Thais de Oliveira (2017)
The theoretical perspectives that have emerged in the post-Cold War emphasized the relevance of the domestic variables in the International Relations Theory study. Considering the ontological changes inside the subdiscipline after 1990, this article aims to analyze the importance of democracy in the hermeneutic scope of the liberal, critical and constructivist theories.